Constitutionalizing Women’s Equality in India: Assessing the Sabarimala Decision - Narain, Vrinda (Columbia Journal of Gender and Law, 2022)
In 2018, in Indian Young Lawyers Association (IYLA) v State of Kerala, popularly known as the Sabarimala case, the Indian Supreme Court struck down a rule that prevented girls and women in the 10-50 age group from entering the Sabarimala temple in Kerala. The Court, in a 4-1 decision, held that the temple rule violated women’s right to equality and right to worship and was not protected under the right to religious freedom. Sabarimala is a landmark decision. For the first time,the Court insisted that all discrimination must be tested against constitutional values and discrimination that perpetuates stereotypes and disadvantage will not withstand constitutional scrutiny. It emphasised the importance of substantive equality in contesting discrimination against women and challenging the structures of oppression that exclude women. Finally, the Court linked women’s equality rights with equal citizenship. Focusing on the Sabarimala decision, this paper evaluates the recognition of women’s rights in Indian constitutional jurisprudence and assesses its transformative potential. The paper aims to place women’s equality rights squarely within constitutional discourse; to further develop understandings of justice that will constitutionalize women’s equality rights and ensure their inclusion in constitutional doctrine and discourse and to create salient changes in women’s everyday lives.